Apela inhibits systemic and renal inflammatory reactions in mice with type I cardiorenal syndrome. Issue 10 (13th September 2021) - Jin, Liangli; Li, Quanyi; Li, Jing; Pan, Yang; Zou, Jue; Wu, Xiaoyuan; Wang, Zhi
Abstract: This study investigated the effect of apela on renal function and anti‐inflammatory effect on whole body and kidney tissue in mice with type I cardiorenal syndrome (CRS). The murine type I CRS model was established and apela was subcutaneously infused for two weeks. Cardiac and renal functions were evaluated by echocardiography and blood biochemistry, respectively. The systemic and renal inflammatory responses were examined with molecular biological and histological methods. Human renal glomerular endothelial cells (RGECs) were used to evaluate the adhesion effect of monocytes in vitro. Compared to mice from the control group (CRS + vehicle), the plasma levels of N‐terminal pro‐brain natriuretic peptide, blood urea nitrogen and creatinine were significantly decreased, while the mean left ventricular ejection fraction was increased in apela‐treated CRS mice at the 4th week. The expression of monocyte chemoattractant protein‐1 (MCP‐1) and tumor necrosis factor‐α (TNF‐α) in the circulation and kidney was decreased in apela‐treated mice compared with control mice, and apela improved cardio‐renal pathology in mice with type I CRS. Additionally, Apela significantly suppressed the expression of MCP‐1, TNF‐α, intercellular adhesion molecule‐1 and vascular intercellular adhesion molecule‐1 in RGECs induced by angiotensin II (Ang II), and inhibited the promoting effect of Ang II on the adhesion of THP‐1 cells to RGECs. Western blot results showed that the expression of phosphorylated nuclear factor kappa B (phospho‐NFκB) in CRS mice was increased, but the expression of phospho‐NFκB was down‐regulated after apela treatment. Furthermore, apela significantly inhibited the Ang II‐mediated increase in phospho‐NFκB expression in RGECs in vitro, but the administration of an apelin peptide jejunum receptor (APJ) inhibitor blocked the inhibitory effect of apela. This study revealed that apela improves cardiorenal function and reduces systemic and renal inflammatory response in type I CRS mice and the apela/APJ system may alleviate renal inflammatory responses by inhibiting the NFκB signalling pathway.